Undergraduate nursing students’ attitude towards mental illness: a cross sectional study - C. Sharma, Ravi; D. Sharma, Dinesh; Kanwar, Neeraj; Kanwar, Pankaj; Manta, Santosh (International Journal of Research in Medical Sciences, 2017)
Background: People suffering from mental illness commonly face stigma, bias, and discrimination by general public. Health care professionals are not immune to social biases and share the public’s attitude meted out to people with mental illness. Nursing students are future health manpower. There are only few studies conducted on medical students’ attitude towards people with mental illnesses in India. We have planned this study to examine the undergraduate nursing students’ attitude towards people suffering from mental illnesses. Methods: It was a cross-sectional study. A total of 220 undergraduate nursing students were selected randomly with their consent to complete the Attitude Scale for Mental Illness (ASMI). Results: The nursing students were found to have a significant positive attitude towards mental illness in five of the six attitudes factors: Restrictiveness (8.42), benevolence (28.6) and stigmatization (7.3), separatism (15.6) and stereotype (9.4) However, these students had negative attitude in pessimistic predictions (12.5) domain as they rated this domain slightly on the higher side. Conclusions: Academic education in this field must be conceptualized and planned in order to favor the change of the attitudes that includes greater utilization of those teaching strategies that challenge beliefs and assumptions and promote a commitment to provide holistic care to people with mental illness.